The Role Of Transformational Leadership In Improving Job Satisfaction - Ida Rianty (UNIVERSITAS PAKUAN, 2018)
The purpose of this study to determine the role of Transformational Leadership in increasing Job Satisfaction. The samples have been taken by random sampling technique selecting amounted to 249 samples from permanent lecturers of private Islamic High School in Jambi Province. This research uses a Sequential Explanatory Design Mixed Method that is first research using a quantitative method then deepen it with a qualitative method. This is intended to result in more in-depth and comprehensive research.The result shows that there is a positive correlation between transformational leadership which has a high effect on job satisfaction of the lecturers. The coefficient correlation is ry = 0,483 and coefficient determination ry = 0,233. It means that 65.90% of job satisfaction is influenced by transformational leadership, and the rest of it influenced by other factors.